Hungarian Monitoring, 18 February 1990 . [Magyar rádiófigyelő], 1990. február 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports on the protests in Bucharest - Mass election rallies in many Soviet cities - Violent protest in the capital of Tajikistan - Japanese election results Domestic Affairs: - Independent Smallholders', Agrarian Workers and Civic Party (FKGP), Hungarian Social Democratic Party election rallies - Interview with József Antall - Interview with Edward Teller on criticisms of his involvement with the hydrogen bomb - Summary of the two-day academic conference "Jews in Hungarian history" - Avant-garde art under Kádár's culture minister György Aczél - Hungarians in Transylvania Economy: - Hungarian National Bank briefing on loans Külpolitika: - Tudósítások a bukaresti tüntetésről - Választási nagygyűlések a SZU több városában - Heves tüntetés Tádzsikisztán fővárosában - A japán választások eredményéről Belpolitika: - FKGP, MSZDP választási nagygyűlések - Antall József interjú - Interjú Teller Edével a hidrogén bombával kapcsolatban őt ért bírálatokról - Beszámoló "A zsidóság a magyar történelemben" című kétnapos tudományos ülésszakról - Az avantgárd művészet az Aczél - Korszakban - Az erdélyi magyarság ügye Gazdaság: - MNB tájékoztató a hitelfelvételekről